Transverse Sinus Stenting Reverses Medically Refractory Idiopathic Intracranial Hypertension - Reid, Kate; Winters, H. Stephen; Ang, Timothy; Parker, Geoffrey D.; Halmagyi, G. Michael (Frontiers in Ophthalmology, 2022)
Aim: To characterise the ophthalmic indications for, and ophthalmic efficacy of, transverse sinus stenting in adults with medically refractory idiopathic intracranial hypertension. Methods: A retrospective cohort study was undertaken on a single-author database of 226 successive patients with confirmed IIH. 32 patients were identified who received a transverse sinus stent for medically refractory disease, which was defined as visual threat and/or intolerance of maximal medical therapy. Patients with medically refractory disease proceeded to stenting, if found to have a significant transverse sinus stenosis gradient at catheter venography. Visual threat was quantified via the degree of papilledema on optical coherence tomography of the retinal nerve fibre layer, and via the visual field mean deviation. CSF opening pressure at lumbar puncture and cerebral venous sinus pressure measurements from catheter venography were correlated with the ophthalmic data, noting also intolerance of maximal medical therapy. Complications of stenting were fully assessed. Results: Medically refractory IIH was found in 18% of the total cohort of IIH patients. 90% of those with medically refractory disease had a significant transverse sinus stenosis pressure gradient, and 80% proceeded to stenting. The intervention eliminated papilledema in 96% of stented patients, and allowed 81% to cease acetazolamide. The need for a further procedure was low at 6%, and the safety profile was favourable. Conclusions: Medically refractory disease in IIH is common (18%), and nearly always associated with a significant transverse sinus stenosis pressure gradient (90%). Endovascular stenting of the stenosis deserves wider uptake as a highly effective, safe and usually definitive treatment. It safeguards vision by eliminating papilledema (96%), and allows most patients to cease acetazolamide (81%). By analogy with glaucoma, if acetazolamide is the prostaglandin of IIH and CSF diversion the emergency glaucoma filter, stenting is the minimally invasive glaucoma surgery.